2014
DOI: 10.1371/journal.pone.0099496
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of SP110 Are Associated with both Pulmonary and Extra-Pulmonary Tuberculosis among the Vietnamese

Abstract: BackgroundTuberculosis (TB) is an infectious disease that remains a major cause of morbidity and mortality worldwide, yet the reasons why only 10% of people infected with Mycobacterium tuberculosis go on to develop clinical disease are poorly understood. Genetically determined variation in the host immune response is one factor influencing the response to M. tuberculosis. SP110 is an interferon-responsive nuclear body protein with critical roles in cell cycling, apoptosis and immunity to infection. However ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
(58 reference statements)
0
22
1
Order By: Relevance
“…Among these articles, 18 articles were designed on animal models; 6 articles were excluded because of the duplicated use of data; 5 articles were excluded because of no case-control design. Two of the ultimately selected articles included data from 4 independent studies 1221. Therefore, 11 articles including 13 studies were included in our meta-analysis, with 9 articles written in English and 2 in Chinese 1218192021223233343536.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these articles, 18 articles were designed on animal models; 6 articles were excluded because of the duplicated use of data; 5 articles were excluded because of no case-control design. Two of the ultimately selected articles included data from 4 independent studies 1221. Therefore, 11 articles including 13 studies were included in our meta-analysis, with 9 articles written in English and 2 in Chinese 1218192021223233343536.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies yielded inconsistent consequences. Abhimanyu, et al,12 Cai, et al,18 and Cong, et al19 identified the association of SP110 polymorphisms with TB by a case-control design while irrelevant results were found by Png, et al20, Fox, et al21, and Jiang, et al22 Thus, we performed a comprehensive review and updated meta-analysis with more SP110 polymorphisms, articles and subgroup analysis than before, and attempted to verify and offer an accurate and comprehensive understanding of the association between polymorphisms of SP110 gene and human TB susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Two single nucleotide polymorphisms (SNPs) of this gene (rs3948464 and rs2114592) were found to be associated with TB in the West African population (8), whereas rs1427294 and rs1135791 have been reported to be significantly associated with TB in India (9) and China (10), respectively. However, similar studies in other populations have not found such association (7). In addition, a metaanalysis of five SNPs could not find a consistent association with TB (11).…”
Section: Introductionmentioning
confidence: 71%
“…Recently, the intracellular pathogen resistance-1 (IPR1) gene located on the supersusceptibility to tuberculosis 1 (sst1) locus has been shown to contribute fundamentally to innate immunity against Mycobacterium tuberculosis infection in a murine model (5). SP110 (51 037 bp on 2q37.1; MIM 604457) is the human homologue of IPR1 and the role of its variants has been implicated in a number of diseases including TB (7). Results of the studies on SP110 gene in the individuals with TB have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Variants in the SP110 nuclear body protein gene (SP110), originally identified as the locus (Ipr1) controlling tuberculosis susceptibility in mice (7), have been associated with human TB susceptibility (8,9), as well as other intracellular bacteria, such as Chlamydia pneumoniae (10). 1) to maximize probability that the SP110 gene would be expressed correctly.…”
Section: Tuberculosis and Genetic Control Of Resistancementioning
confidence: 99%